Navigating gender and sexuality in the classroom: Narrative insights from students and educators - McEntarfer, Heather Killelea (Routledge, 2016)
Gender identity and sexuality play crucial roles in the educational experiences of students, parents, and teachers. Teacher education must more directly address the ways that schools reflect and reproduce oppressive gender norms, working to combat homophobia, transphobia, heteronormativity, and gendered expectations in schools. This volume examines teacher candidates’ experiences with gender and sexuality in the classroom, offering insight and strategies to better prepare teachers and teacher educators to support LGBTQ youth and families. This volume addresses the need for broader, more in-depth qualitative data describing teacher candidates’ responses to diversity in the classroom (including gender, sexuality, race, class and religion). By using pedagogical tools such as narrative writing and positioning theory, teacher candidates explore these issues to better understand their own students’ narratives in deeply embodied ways. This book calls for schools to be places where oppression, in all its complexity, is explored and challenged rather than replicated.
Keywords: LGBTQIA2+; approches et analyses; discipline; formations; hétérosexisme; identités LGBTQIA2+; intersectionnalité; outils; outils didactiques; privilèges; pédagogie; religion; sciences de l'éducation; sexualité; systèmes d'oppressions; thématiques

Se retrouver entre soi pour se reconnaitre: conceptions du genre et regulation des echanges dans un forum de personnes trans - Pastinelli, Madeleine; Dery, Caroline (Anthropologie et Societes, 2016)
Les possibilités de communication anonyme permises par les nouvelles technologies amènent des personnes qui ont en commun des pratiques ou des expériences qui les stigmatisent à se retrouver à l’abri des regards pour échanger entre elles et former des communautés en ligne. Ce faisant, elles se réapproprient leur expérience dans un langage choisi qui leur permet de redonner sens à des identités et des pratiques marginales ou considérées comme déviantes ou pensées comme relevant de la pathologie par le discours médical. L’enquête que nous avons menée dans une communauté en ligne de personnes trans éclaire la manière dont la fréquentation de celle-ci permet à ces personnes de se (re)connaître dans leur expérience particulière du corps et du genre et de faire sens de cette expérience. La volonté communément partagée par ces personnes de penser autrement leur expérience donne lieu à la rencontre d’une multitude de conceptions différentes, et parfois incompatibles entre elles, de l’identité de genre et de l’expérience trans. L’analyse se penche plus particulièrement sur la régulation du discours et des échanges qui est faite par les modérateurs dans ce contexte et sur le type de consensus qu’elle rend possible.
Keywords: 2000 à aujourd'hui; 2010-2019; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; corps; cours; discipline; hétérosexisme; identités LGBTQIA2+; outils; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; sciences humaines; soc3113; sociologie; systèmes d'oppressions; thématiques; transféminisme

Queer inclusion in teacher education: Bridging theory, research, and practice - Murray, Olivia J. (Routledge, 2015)
Queer Inclusion in Teacher Education explores the challenges and promises of building queer inclusive pedagogy and curriculum into teacher education. Weaving together theory, research findings, and practical "how-to" strategies and materials, it fills an important gap by offering a clear roadmap and resources for influencing the knowledge, beliefs, and actions of faculty working with pre-service teachers. While the book has implications for policy change, most immediately, readers will feel empowered with ideas for faculty development they can implement in their own teacher education programs. Looking at both the politics and practices of teacher education and the ways in which queer issues manifest in schools, it is hopeful in suggesting that if teachers and pre-service teachers can critically reflect on homophobia and heteronormativity, they can begin to think about and relate to queer youth in a different, more positive and inclusive way. A Companion Website [http://queerinclusion.com] with additional activities and materials for teacher educators and faculty development and a practical guide enhances the usefulness of the book.
Keywords: LGBTQIA2+; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; outils; ouvrages de références; pédagogie; pédagogie queer; queer; sciences de l'éducation; systèmes d'oppressions; systèmes éducatifs; thématiques

Gay and lesbian literature in the classroom: Can Gay themes overcome heteronormativity? - April M Sanders; Janelle B. Mathis (Journal of Praxis in Multicultural Education, 2013)
Lesbian, gay, bisexual, and transgender (LGBT) characters do exist in children’s and young adult literature, yet there is a lack of classroom exposure to such literature. Educational organizations have realized the need for dispelling prejudices about LGBT people by including such texts in the classroom as well as discussions regarding LGBT themes and characters in the books. Yet the practice of simply including diverse texts without discussing LGBT issues could cause greater marginalization for students because the silence regarding LGBT issues and characters encourages the practice of heteronormativity. This inquiry examined a range of children’s and adolescent books that could be used in classroom discussions to develop insight about LGBT themes and characters in order to understand if the texts were saturated with LGBT themes and characters to the point that teachers and students could not avoid the LGBT factors while reading.
Keywords: amériques; approches et analyses; discipline; hétérosexisme; identités LGBTQIA2+; pédagogie; ressource en ligne; régions géographiques; science de l'éducation; systèmes d'oppressions; thématiques; états-unis

Minorités sexuelles, Internet et santé - Lévy, Joseph J. (Presses de l'Université du Québec, 2011)
Les nouvelles technologies de communication, et notamment Internet, ont transformé à la fois les stratégies relationnelles et la transmission et le partage des informations dans toutes les sphères de la vie, incluant le domaine de la santé. Pour les minorités sexuelles qui sont confrontées à de multiples formes de discrimination et de marginalisation, Internet est devenu un puissant moyen de s’organiser, d’informer et d’intervenir dans le champ de la santé. Les associations et organismes communautaires ciblant ces populations proposent aujourd’hui un ensemble de sites et de stratégies de soutien et d’intervention. Ces outils synchrones et asynchrones disponibles en ligne visent l’amélioration de la santé mentale et physique, des relations interpersonnelles et la prévention des ITSS et du VIH/sida. Par contre, les usages qui varient en fonction des populations LGBT peuvent aussi concourir à la prise de risques et à des formes de dépendance. Afin de mieux comprendre les enjeux entourant les usages d’Internet et la santé, cet ouvrage, réalisé grâce à l’appui de l’équipe pancanadienne Sexualités et genres ;: vulnérabilité et résilience (SVR), regroupe les contributions de chercheurs de l’équipe qui ont effectué des travaux sur Internet et la santé ainsi que d’intervenants impliqués dans des organismes communautaires, qui utilisent des sites Internet à des fins de réseautage, de transfert d’informations et d’interventions en ligne dans les contextes québécois et canadien.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; canada; cours; discipline; hétérosexisme; internet; militance; médecine; organisme communautaire; premier cycle; pédagogie; périodes historiques; queer; québec; régions géographiques; réseaux sociaux; santé; sciences de la santé; sciences humaines; sexualité; soc2014; système médical; systèmes d'oppressions; thématiques; travail social